High-fructose consumption and metabolic diseases - Trindade, Cleide E.P. [UNESP]; Kurokawa, Cilmery [UNESP]; Barreiros, Rodrigo C.; Bossolan, Grasiela [UNESP] (My University, 2012)
Renewed interest in the study of fructose arose after a number of papers on the harmful effects of ingesting high-fructose diets were published. Fructose intake has increased significantly in the United States and worldwide in the last four decades, which is mainly due to the increased consumption of high-fructose corn syrup and sucrose as a sweetener in beverages and in industrialized foods. There is substantial evidence from studies on rodents and on human adults suggesting that fructose intake in large amounts and for a long period of time leads to the development of the metabolic syndrome, insulin resistance, and dyslipidemia with increased plasma triacylglycerol, phospholipids and de novo lipogenesis. As a consequence, fructose may contribute to increased obesity, hyper-tension, type-2 diabetes and cardiovascular diseases. Fructose is a monosaccharide found in fruit, some vegetables and honey. Sucrose, a natural sweetener found in sugar cane and beets (50% fructose), is a disaccharide with two hexoses, one glucose molecule bonded to a fructose molecule by an alpha-1-4 glycoside. Although fructose has the same chemical formula as that of glucose (C6 H12 O6), it differs in its structure and metabolism. In the last few decades, sweeteners have been produced by corn starch hydrolysis, and part of the glucose produced is changed into fructose by enzymatic isomerization. This high-fructose corn syrup (42%-55% fructose) has a lower price than sucrose, and it has in-creasingly replaced sucrose as a sweetener in beverages and industrialized foods.Fructose can be produced from glucose by the sorbitol pathway. In endogenous fructose production, non-phosphorylated glucose is converted into fructose. Initially, glucose produces sorbitol in a reaction catalyzed by aldose reductase. In the next step, fructose is formed from sorbitol in a reaction catalyzed by sorbitol dehydrogenase. This pathway may be important in the embryonic stages of human life for regeneration of pyridine nucleotides in order to maintain ATP concentrations and cellular redox potentials when the fetus is in a low oxygen environment. After absorption, fructose is rapidly extracted by the liver and metabolized into fructose-1-phosphate in a reaction catalyzed by fructokinase, which is specific for fructose. Subsequently, fructose-1-P is split by fructose-1-phosphate aldolase in trioses, dihydroxyacetone phosphate and glycer-aldehyde, a pathway to provide the backbone for triacylglycerol and phospholipid syn-thesis. Triose-P is converted into glucose and glycogen as well as into lactate, which can produce plasma lactic acidosis, and into glycerol, a precursor for triglycerides and de novo lipogenesis. Although considerable evidence suggests that high fructose intake can produce harmful effects, investigations where high-fructose diets are compared with high-glucose diets are necessary to clarify the real role played by free fructose in adverse metabolic effects. In epidemiological studies, the analysis of the effects of high-fructose corn syrup and high sucrose intake must consider that both products are composed of fructose and glucose. © 2012 by Nova Science Publishers, Inc. All rights reserved.